PREVALENSI DAN KORELASI INSOMNIA TERHADAP KEMAMPUAN KOGNITIF REMAJA USIA 15-18 TAHUN DI PANTI ASUHAN WIDHYA ASIH 1 DENPASAR - Rimbawan, Pande Putu Gede Krisna Bayu Pramana; Ratep, Nyoman (E-Jurnal Medika Udayana; Vol 5 No 5 (2016): E-jurnal medika udayana, 2016)
The advances in technology and changes in lifestyle on society, especially teenagers resulted in changes to the sleep cycle that is very disturbing in productivity, quality of life and cognitive ability. Many teenagers complained have few hours of sleeping and difficult to awaken in the morning so they feel very weak and sleepy during the day. Many activities and complexity to the identity of teenagers causing this age group are particularly vulnerable to have sleeping disorders, insomnia. The purpose of this study was to determine the prevalence of insomnia and its correlation to the cognitive abilities of teenagers age 15-18 years, living in Widhya Asih 1 Denpasar orphanage. Subjects were 21 teenages age 15-18 years, which consisted of 10 men (47.6%) and 11 women (52.4%). The study used cross sectional, in addition to demographic data, diagnostic criteria for insomnia using Sleeping Disturbance Scale for Children (SDSC) and cognitive diagnostic using the Mini Mental Status Examination (MMSE). Data were analyzed by data processing SPSS version-17. The prevalence of insomnia on teenagers in Widya Asih 1 Denpasar orphanage were 100%, which were 47.6% had mild insomnia and other 47.6% experienced moderate insomnia. Only 4.8% were experiencing severe insomnia based on the SDSC score. Teenager with severe insomnia suffered from scoliosis and pulmonary complications that cause her sleep quality was very bad. In the MMSE test almost all teenagers were in the normal range, but only one sample got a score of 22 (probable cognitive impairment).
Keywords: insomnia, cognitive ability, teenagers, SDSC, MMSE